Allogenic Bone Marrow Transplantation for Children with Philadelphia Chromosome-Positive Acute Lymphoblastic Leukemia - OHNO, Toshiyuki; SUZUKI, Tatsuhito; ANDOH, Tsunesaburoh; WADA, Yoshiro; HIRABAYASHI, Noriyuki; YAZAKI, Makoto; MIZUNO, Mihoko (The Japanese Journal of Pediatric Hematology, 1990)
Two cases of allogenic bone marrow transplantation (BMT) for children with Philadelphia chromosome (Ph1) -positive acute lymphoblastic leukemia were reported. The first case was a 13-year-old boy who received BMT from an HLA genotypically identical brother in the first remisson. The second case was a 7-year-old boy who received BMT from an HLA-A, B, and DR matched and MLC positive mother in the third remission. In this latter case, chromosomal analysis revealed that chromosome of leukemic cells in the first admission was normal, but chromosome at the first bone marrow relapse was Ph1-positive. He relapsed again in central nervous system (CNS) at 3 months of second complete remission (CR), and BMT was done following the therapy of CNS leukemia. The first case was conditioned with cyclophosphamide (CY) 60 mg/kg×2, araC 3 g/m2×3, and total body irradiation (TBI) 10 Gy. The second case was conditioned with CY 60 mg/kg×2, araC 3 g/m2×4, and TBI 10 Gy plus 6 Gy of craniospinal irradiation. The first case received cyclosporine A (CyA) and the second case received CyA and methotrexate for graft-versus-host desease (GVHD) prophylaxis. The first case had grade II of acute GVHD, chronic GVHD, and interstitial pneumonia, and is free of leukemia at 39 months after BMT with 100% Karnofsky performance scale. The second case had grade I of acute GVHD, chronic GVHD, and is free of leukemia at 8 months after BMT. Allogenic BMT for children with Phi-positive ALL should be done if a suitable marrow donor is available.